A Study on $φ$-Symmetric $τ$-curvature tensor in $N(k)$-contact metric manifold - Ingalahalli, G.; Bagewadi, C.S. (Carpathian Mathematical Publications, 2014)
In this paper we study $τ$-curvature tensor in $N(k)$-contact metric manifold. We study $τ$-$φ$-recurrent,$τ$-$φ$-symmetric and globally $τ$-$φ$-symmetric $N(k)$-contact metric manifold.